2013
DOI: 10.4314/tjpr.v12i2.13
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Cinnamomum tamala Extract on Gentamicin-Induced Nephrotic Damage in Rabbits

Abstract: Purpose: To investigate the reno-protective properties of Cinnamomum tamala against gentamicininduced nephrotoxicity in rabbits.Methods: Rabbits were randomly divided into four groups (n = 6) including Group-1 (normal saline), 80 mg/kg/day), 200 mg/kg/day) and 80 mg/kg/day and C. tamala, 200 mg/kg/day

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…Histological changes accompained by gentamicin treatment vary from renal tubular epithelium cell necrosis, necrotizing glomeruli and atrophic of glomeruli. These results showed agreement with (47,48,49). Researchers have shown that gentamicin caused apoptosis in glomeruli and tubules in which gentamicin led to a significantly increased in the amount of cleaved caspase 3, Bax, and p53 protein expression while it decreased the Bcl-2 protein expression (50).…”
Section: Discussionsupporting
confidence: 88%
“…Histological changes accompained by gentamicin treatment vary from renal tubular epithelium cell necrosis, necrotizing glomeruli and atrophic of glomeruli. These results showed agreement with (47,48,49). Researchers have shown that gentamicin caused apoptosis in glomeruli and tubules in which gentamicin led to a significantly increased in the amount of cleaved caspase 3, Bax, and p53 protein expression while it decreased the Bcl-2 protein expression (50).…”
Section: Discussionsupporting
confidence: 88%
“…of rat. While Ullah et al 30 also found co-supplementation of cinnamon plus gentamicin at highest concentration improved the kidney profile in rats and suggested antioxidant effects of cinnamon are due to the presence of the copious amount of phenolic and flavonoid contents. Several recent studies have described a direct relationship between the oxidant stress induced by toxins or metal nanoparticles and its characterization by determination of the activity of oxidative stress-related biomarkers (MDA, LPO, CAT, and GSH).…”
Section: Discussionmentioning
confidence: 97%
“…GM is a commonly used antibiotic aminoglycoside that has been shown to cause significant histological harm, particularly in renal proximal convoluted tubules. (46), (47) and (48). Extensive and major lesions of the renal system including tubular necrosis and inflammatory cell infiltration (49), shrinkage of the glomeruli, dilated and congested intertubular blood vessels and haemorrhage Vol.…”
Section: Effect Of Gentamicin and Ethanolic Extract Of Petroselinum Cmentioning
confidence: 99%